SAT-195 The Diagnosis and Management of a Functional Paravertebral Paraganglioma - Findlay, Ryan (J Endocr Soc, 2020)
A 32-year-old male presented with a 4-year history of palpitations, diaphoresis, and orthostatic hypotension. One year prior to presentation, he began experiencing severe, episodic headaches and neck pressure. Neurological work-up included an MRI head, neck, and spine, identifying a left posterior mediastinal lesion adjacent to the T5 vertebral body, approximately 2.4 x 2.0 cm. A community surgical center attempted mass resection via Video -assisted (VATS) approach. Resection was aborted intraoperatively due to a hypertensive crisis following lesion manipulation, with his systolic blood pressure increasing above 325 mmHg. Subsequent evaluation revealed a 24-hour urine norepinephrine of 6117 nmol/d (normal <575) and normetanephrines of 16.6 umol/d (normal <3.4). An MIBG study showed intense tracer avidity in the left paraspinal lesion and minimal uptake in the adrenal glands. A functional paravertebral paraganglioma was diagnosed and the patient was initiated on alpha and beta-blockade in preparation for staged combined treatment. Spinal angiography was performed to define the arterial supply of spinal cord and tumor, which confirmed a hypervascular left thoracic paraspinal tumor. Arterial supply emanated from the left T4 intercostal and left supreme intercostal arteries and a prominent draining vein was present. Trans-arterial particle embolization was performed via both arteries with minimal residual tumor blush present post procedure. Successful VATS excision of the tumor was completed one week after arterial embolization with minimal blood loss. Pathology of the resected tumor revealed an overall intact tumor that stained diffusely positive with synaptophysin and sustentacular cells highlighted by S100 protein with a few foci of coagulative necrosis. Episodes of hypertension (maximum BP 210/80) occurred during embolization and surgical resection with vascular manipulation. These were managed with intraoperative nitroprusside and phentolamine. Peri-procedural plasma metanephrine and cathecholamine levels were collected. Normetanephrine levels (normal <=0.89 nmol/L) were 4.66 before embolization, >6.25 after embolization, 3.70 the day after embolization, 4.10 before VATS, and 0.69 after VATS. Norepinephrine levels (normal 0.8–3.4 nmol/L) were 24.3, 111.7, 61.1, 19.6, and 4 respectively. Genetic testing showed no hereditary predisposition. Discussion: Functional neuroendocrine tumours may be difficult to diagnose due to the wide variety of clinical presentations and must be considered when investigating a vascular mediastinal tumor. In our case, pre-operative embolization did not normalise plasma catecholamine levels, likely from incomplete arterial embolization, but helped reduce intra-operative surgical bleeding risk. Alpha- and beta-blockade should be continued until surgical resection, with dose adjustment as required.